A corner of the universe [compact disc, unabridged] - Martin, Ann M., 1955- (Listening Library, 2003)
The summer that Hattie turns twelve, she meets the childlike uncle she never knew and becomes friends with a girl who works at the carnival that comes to Hattie's small town.